INTERCULTURAL ASPECTS IN TEACHING INDONESIAN AS A FOREIGN LANGUAGE (BIPA) - Winasti Rahma Diani; Sisilia Setiawati Halimi (Universitas Islam Sumatera Utara (UISU), 2020)
Learners should be intercultural speakers in foreign language teaching that promotes the intercultural dimension. In mastering the intercultural competencies, students are expected to be able to position themselves based on the background of their origin cultures and the culture that they learn in intercultural situations. This study aimed to find out how teaching the intercultural competencies was implemented in the course of Indonesian as a Foreign Language (BIPA), especially at the beginner level. This study investigated the intercultural teaching through textbooks, classroom observation, cultural program, and assessment used for the beginner course at the Institution X. The results of the analysis showed that the textbooks used contain themes of intercultural learning for the survival needs of novice students. The results of the classroom observation also showed that intercultural teaching was well executed. However, the results of the field trip observations that were part of the cultural program showed that the activities were not integrated with language learning. Besides, the results of the assessment analysis indicated that the exercise books and the tests used were not considered as the intercultural aspects. Therefore, this study is expected to provide input for intercultural teaching in BIPA courses, especially at the beginner level.